Impacto de práticas silviculturais sobre a diversidade de formigas (Hymenoptera Formicidae) em eucaliptais - Ramos, Lucimeire de Souza (2001)
It was aimed to know and compare the diversity of ants in native vegetation of cerrado and in eucalyptus plantations through ecological indicators as well as to verify the effect of the systematic or localized control of leaf-cutting ants and chemical or mechamical hoeing on the ants commumity. The work was accomplished in the town of Bom Despacho (MG), CAF Santa Barbara Ltda enterprise. The ants were collected by utilizing the winkler extractor and afterwards were screened, mointed and identified. A total of 129 species was collected. The Shannon-Winner diversity index and Chao 2 richness estimator revealed that the systematic control of leaf-cutting ants reduced more the diversity of ants than the localized control and mechanical hoeing more than the chemical one. High similarity occurred among the areas intended to the systematic and localized control in time, being that the first one decreased from 8 to 60 days and the second one only at 8 days. Verifying that the effect of the hoeings is more immediate over the ants community. Sericomyrmex sp 01 and Solenopsis (Diplorhopthrum) sp 01 were the dominant in the eucalyptus plantations and in the native vegetation, respectively. The ants collected were classified into seven guilds. Pheidole fallax, Solenopsis (Diphorhopthrum) sp 01, Mycocepurus goeldii and Brachymyrmex sp 01 were indicators of impact caused both by mechanical and chemical hoeings. The ants were more susceptible to the systematic control while elemination of the undestoory did not cause great harmful effects on them.